Potential contributions of the intrinsic retinal oscillations recording using non-invasive electroretinogram to bioelectronics - Rodríguez-Arzate, Cynthia Alejandra; Noguez-Imm, Ramsés; Reyes-Ortega, Pamela; Rodríguez-Ortiz, Luis Roberto; García-Peña, María Fernanda; Ordaz, Rainald Pablo; Vélez-Uriza, Fidel; Cisneros-Mejorado, Abraham; Arellano, Rogelio O.; Pérez, Claudia I.; Hernández-Zimbrón, Luis Fernando; Dégardin, Julie; et al. (Frontiers in Cellular Neuroscience, 2024)
Targeted electric signal use for disease diagnostics and treatment is emerging as a healthcare game-changer. Besides arrhythmias, treatment-resistant epilepsy and chronic pain, blindness, and perhaps soon vision loss, could be among the pathologies that benefit from bioelectronic medicine. The electroretinogram (ERG) technique has long demonstrated its role in diagnosing eye diseases and early stages of neurodegenerative diseases. Conspicuously, ERG applications are all based on light-induced responses. However, spontaneous, intrinsic activity also originates in retinal cells. It is a hallmark of degenerated retinas and its alterations accompany obesity and diabetes. To the extent that variables extracted from the resting activity of the retina measured by ERG allow the predictive diagnosis of risk factors for type 2 diabetes. Here, we provided a comparison of the baseline characteristics of intrinsic oscillatory activity recorded by ERGs in mice, rats, and humans, as well as in several rat strains, and explore whether zebrafish exhibit comparable activity. Their pattern was altered in neurodegenerative models including the cuprizone-induced demyelination model in mice as well as in the Royal College of Surgeons (RCS–/–) rats. We also discuss how the study of their properties may pave the way for future research directions and treatment approaches for retinopathies, among others.